Assessing the quality of social media data: a systematic literature review - Oumaima Reda; Ahmed Zellou (Institute of Advanced Engineering and Science, 2023)
In recent years, social media have been at the heart of new communication technologies. They are no longer used only to facilitate interaction between family, friends, and professional relationships, but tend to become an increasingly used communication channel to address public opinion. Research involving data sources from social media are relatively a recent and expanding area of research, nevertheless, the literature remains limited regarding the complex issue of how to assess and ensure the quality of social media data significantly and adequately. Our goal in this study is to provide a clearer and deeper understanding and a comprehensive overview of the existing state of research pertaining to the assessment of data quality in social media context. We performed a systematic literature review (SLR) on the quality of social media data to collect, analyze, and discuss data on the accuracy and value of prior literature that has focused on this area, has addressed a variety of topics, and has been published between 2016 and 2021. We followed a predefined review process to cover all relevant research papers published during this period. Our results demonstrate and strengthen the significance and the importance of data quality especially in the context of social media.